COVID-19 vaccine and its effect on sperm - Rujittika Mungmunpuntipantip; Viroj Wiwanitkit (Bioscientifica, 2023)
We would like to share ideas on the recent article by Meitei et al. (2022) published in this journal. The authors reported that the baseline sperm parameters of 20 (38%) of their patients were below the WHO standard range; nevertheless, no significant reduction in ejaculate quality was found in their follow-up samples. Meitei et al. (2022) also found that no ejaculates in either study group were azoospermic during the follow-up evaluation. The findings in this report confirm that the Covishield™ vaccine has no negative effects on male fertility (Meitei et al. 2022). We are all concerned that, despite its benefits, COVID-19 immunization could be harmful. It is difficult to determine the exact clinical link because there is minimal information on the health and andrological status of vaccine recipients prior to inoculation.